Pengaruh Operating Capacity, Leverage, Liquidity, dan Firm Size Terhadap Financial Distress pada Perusahaan Sektor Consumer Cyclical Sebelum, Saat dan Sesudah Pandemi Covid-19 - Lailatun Hasanah; Regina Jansen Arsjah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the effect of operating capacity, leverage, liquidity, and firm size on financial distress in cyclical consumer sector companies before, during, and after the COVID-19 pandemic. This study uses a quantitative approach and the research data uses financial reports from 60 companies with the largest total assets listed on the Indonesia Stock Exchange during the period 2018-2023. The results showed that operating capacity has a negative and insignificant effect on financial distress before the pandemic, but has a significant positive effect on financial distress during and after the pandemic. Leverage and Firm size have a positive effect on financial distress before the pandemic, but this effect becomes negative during and after the pandemic. Liquidity has a positive effect on financial distress before, during and after the pandemic.